Systematic coarse-graining of sequence-dependent structure and elasticity of double-stranded DNA - Enrico Skoruppa; Helmut Schiessel (Physical Review Research)
Coarse-grained models have played an important role in the study of the behavior of DNA at length scales beyond a few hundred base pairs. Traditionally, these models have relied on structurally featureless and sequence-independent approaches, such as the twistable wormlike chain. However, research over the past decade has highlighted the substantial impact of DNA sequence even at the kilobase pair scale. Several robust sequence-dependent models have emerged, capturing intricacies at the base pair-step level. Here we introduce an analytical framework for coarse-graining such models to lower resolution representations while preserving essential structural and dynamic features, enabling the efficient sampling of large molecules. When considering both rotational and translational degrees of freedom, coarse-graining is shown to yield excellent results up to about one helical repeat. For scenarios where the local stretch modulus is inconsequential, this range can be significantly increased by only considering the rotational degrees of freedom, which permits faithful coarse-grained representation up to several helical repeats. Rather than providing a fully parametrized model, we present the methodology and software necessary for mapping any base pair-step model to the desired level of coarse-graining. Finally, we provide application examples of our method, including estimates of the persistence length and effective torsional stiffness of DNA in a setup mimicking a freely orbiting tweezer, as well as simulations of helically curved DNA.